Peranan Statistika dan Pengembangan Karakter dalam Menghadapi Tantangan Era Revolusi Industri 4.0 dan Big Data pada SMAN 1 Praya - Agus Kurnia; Mustika Hadijati; Desy Komalasari; Nurul Fitriyani (Jurnal Gema Ngabdi, 2020)
The development of science and technology provides changes to every aspect of human life including social, economic, educational and industrial changes which are now entering stage 4.0. The Era of the Industrial Revolution 4.0 is identical to the Internet of Things which produces Big Data that cannot be processed with conventional devices and requires special analysis. These changes require human resource development in science, education and character in order to continue to compete with the global world, especially the younger generation who will fill the industrial forward. The problem arises because most of the educational outcomes lack a link and match or a good match between tertiary education which causes students to feel wrong about their majors or the incompatibility of their needs and abilities in the industrial world which makes it difficult for them to find a work. Therefore, coaching efforts are needed so that students can be aware and prepare themselves to improve their quality both by increasing hardskills and soft skills to meet these needs. This community service activity is carried out by SMAN 1 Praya as one of the best high schools and is a reference school in West Nusa Tenggara. The method used is the direct learning method that is evaluated using self-assessment techniques conducted by students using google form. Evaluation results show an increase in students' knowledge of statistics and character development needed in the face of the industrial revolution 4.0 and Big Data after they have participated in this dedication activity.